Dynamic spectrum access using cognitive radio utilizing GNU radio and USRP - A. Rashid, Rozeha (2011)
The thirst for spectrum usage is very demanding specifically due to the explosion of new wireless technologies and services. The current static spectrum allocation policy cannot support the need of this demand and it needs to be revised to allow spectrum to be accessed dynamically. Spectrum utilization can be significantly improved by adopting the concept of Dynamic Spectrum Access (DSA) where unlicensed or cognitive users (CUs) can temporarily utilize a spectrum hole for a period of time and move to another spectrum hole whenever the licensed user appears. In this work, cognitive radio (CR) technology is chosen to provide DSA due to its features of able to sense, learn, adapt and react according to the environment. The proposed design of the CR system for DSA consists of four main functional blocks: spectrum sensing, spectrum management, spectrum decision and data transmission. The implementation is done using GNU Radio and USRP SDR platform. The GMSK based radio equipped with DSA capability using CR technique has been developed and implemented. The results show a significant improvement in term of Packet Reception Rate (PRR) in CR with DSA systems.